The Biological Basis of Cellular Diabetes Mellitus - Alnaji, Abbas (Journal of Advanced Cytology, 2018)
This letter presents a clinician's perspective on the biological basis of diabetes mellitus at the cellular level. Drawing on neurosurgical practice, the author argues that persistent dysglycemia hinders recovery and may reflect long-standing intracellular processes, calling for causal, interdisciplinary management beyond symptomatic care. The piece outlines testable hypotheses and invites further laboratory validation.
Keywords: Diabetes Mellitus; Biological Basis; Cellular; Dysglycemia; Intracellular